Development of Sustainability-Based Marketing Strategy for UMKM Stores Sembako Berkah Makmur: Feasibility Study in South Cikarang - Setyaningrum, Retno Purwani; Pradensha, Desta Vio; Prabowo, Sayo Yoschicho; Raymoundu, Revan; Alfarizi, Naufal Rafi; Erlangga, Subhan Dewa (Review: Journal of Multidisciplinary in Social Sciences, 2025)
The community's need for affordable and easily accessible basic necessities has become , Revan great opportunity for the development of grocery store business. Through the community service program This community, assistance and improvements were provided to the Berkah Makmur Grocery Store in the KSB Housing area, Serang Baru. The aim of this activity is to improve operational effectiveness and strengthening the store's marketing strategy to be able to compete and develop sustainably. This study uses a qualitative method which includes field observations, problem analysis, implementation of digital-based solutions and innovative services, and evaluation of results. In addition, to analyze problems and The potential that can be developed from the Berkah Makmur Grocery Store is also carried out SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach which aims to to formulate the right strategy for business actors. The solutions implemented include: digitalization of stock recording, rearranging store layouts, active promotion through social media, development of delivery services, as well as the creation of customer loyalty programs. Results devotion shows an increase in turnover of 15% in one month, increase in new customer visits by 25%, as well as significant improvements in speed of service. This finding proves that the development of small businesses can done effectively through simple innovations that focus on customer needs and utilization of easily accessible technology. This program is expected to be a model for development of similar businesses in other communities.